Khaldunian Techniques of Historical Criticism and their Place in Modern Debates on Naqd al-Matn (Content criticism) of Hadith - Kozhithod, Salahudheen (İbn Haldun Çalışmaları Dergisi, 2018)
Techniques of Historical criticism developed by Ibn Khanldun in his seminal work al-Muqaddimah are well-known. However, he himself admitted that they are not applicable as such to Hadith criticism instead it should be done by applying techniques of Jarh wa al-Ta’dil (criticism of chain of narration). Nevertheless he rejected many popular ahadith such as the ahadith on advent of Imam Mahdi and Pophetic Medicine. One of the major accusations of the western scholars such as Goldziher was that the early hadith scholars had not applied historical criticism in hadith rather they were exclusively sticking to sanad criticism. Many contemporary Muslim scholars are very much influenced with this criticism and stand for a free and open content criticism of Hadith which creates a tendency to reject several well-authentic ahadith of the Prophet. Here the researcher examines the possibility of applying techniques of historical criticism in hadith and it also examines why Ibn Khaldun differentiated between hadith and history whereas Historiography and ḥadith are both historical account reported through certain chains of narrators. As both are mainly known to us through narration, they are prone to misrepresentations and misinterpretations. It uncovers that to some extent the Khaldunian Techniques are applicable to hadith along with sanad criticism but unlike contemporary scholars they did not stand for an open and free criticism.